Control by an identified modulatory neuron of the sequential expression of plateau properties of, and synaptic inputs to, a neuron in a central pattern generator - Nagy, F (J Neurosci, 1988)
Recordings from the lateral gastric (LG) neuron, which forms part of the gastric mill central pattern generator in the red lobster, Palinurus vulgaris, indicate that regenerative membrane properties (plateau properties) and synaptic inputs interact sequentially rather than simultaneously to determine its discharge pattern. LG thus presents a composite discharge, consisting of 2 separate segments of firing and one silent period. The first firing segment depends on regenerative membrane properties; this is the endogenous component, or segment, of LG's discharge. The second firing segment is the result of extrinsic synaptic input, forming the synaptic component of LG's discharge. The relative importance of these 2 components can vary, and thus LG's discharge ranges from one in which LG fires only as a result of its endogenous component to one in which its endogenous component is entirely absent and only the synaptic component underlies action potentials. Activity in an identified modulatory neuron suppresses the endogenous segment and enhances the synaptic segment of LG's discharge. This long-lasting effect in turn changes phase relationships within the gastric mill network and provides mechanisms for producing flexibility in the gastric pattern generator and for ensuring that a specific motor output is generated by a flexible neural network.